ANALISIS NILAI – NILAI PENDIDIKAN DALAM FLIM “STIP DAN PENCIL ”KARYA ARDY OCTAVIAND - Irwan Soulisa; Anastasia Kairupan; Ledy Sagrim; Ellen Wayori (SOSCIED, 2021)
This study attempts to describe anything nilai-nilai education on film and pencil work ardy octaviand stip .In a qualitative description of this research .Uses the observation of data collection , documents used to film , researchers chose analysis techniques is because our analysis of the data used in this research will be qualitative analysis with data analysis .Based on the results of this study found , education nilai-nilai analyzed in film sip and pencil ardy octaviand according to work friday , the education jenis-jenis (1) consisting of religious values , (2) social values , (3) values .In the film that is shown the form of religious, one / sincerity .The form of the: unyielding moral, bersungguh-sungguh, honesty, struggle and responsibilities .The form of social and friendship and love